Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan - Imanuel, Haryo Crysti; Ali, Rustan; Alimuddin, Firman; Anggerwati, A. Indah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
The purpose of this study is: (1) To determine the partial influence of leadership style and work motivation variables on employee performance at PT Pos Indonesian Parepare Branch. (2) To determine the simultaneous influence of leadership style and work motivation variables on employee performance at PT Pos Indonesian Parepare Branch. In this study, the analysis used was validity test, reliability test, multiple linear regression, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R2) to determine the hypotheses in this study. The sample used in this study was 30 employees at PT Pos Indonesian Parepare Branch. The leadership style variable (X1) does not have a partial effect on employee performance (Y) at PT Pos Indonesian Parepare Branch. This is evidenced by the significant value of 0,054 > 0,05 and (2,015 < 2,051). The work motivation variable (X2) has a partial effect on employee performance (Y) with a significant value of 0,001 < 0,05 and (3,946 > 2,051). Based on the test results on leadership Style and Work Motivation, it was found that 36,249 > 3,350 and the level of 0,000 < 0,05, it was concluded that the independent variables have a simultaneous effect. The correlation coefficient value is 0,854 and the coefficient of determination (R2) = 0,729 (72,9). This means that the leadership style and work motivation variables explain changes in employee performance by 72,9 while there are other variables that influence employee performance by 27,1%.